Peripheral Eosinophil Count May Be the Prognostic Factor for Overall Survival in Patients with Pancreatic Ductal Adenocarcinoma Undergoing Surgical Treatment - Wojciech Ciesielski; Izabela Kupryś-Lipińska; Anna Kumor-Kisielewska; Oliwia Grząsiak; Julia Borodacz; Sebastian Niedźwiecki; Piotr Hogendorf; Adam Durczyński; Janusz Strzelczyk; Alicja Majos (Biomedicines)
(1) Background: The importance of total eosinophil count in peripheral blood (EOS) as a type 2 inflammation marker is known to be fundamental in asthma, chronic sinusitis, and vasculitis. In cancer, despite their questionable antiproliferative effect, their role remains unclear. Our purpose was to describe the relationship between baseline blood EOS and overall survival (OS) in pancreatic ductal adenocarcinoma (PDAC) patients. (2) Methods: We retrospectively analyzed data from 137 adult patients who underwent surgical treatment for pancreatic ductal adenocarcinoma (PDAC) between the years 2012 and 2019. Patients with no recent history of systemic steroid use and without intraoperative metastases were included. Patients were categorized into two groups based on EOS (≥0.1 G/l and <0.1 G/l). Survival outcomes were analyzed using Cox proportional hazards regression models. (3) Results: According to EOS and PDAC stage, median OS values were as follows: in stage I–III, EOS ≥ 0.1 G/l group: 14.5 months, in stage I–III, EOS < 0.1 G/l group: 8.0 months, in stage IV, EOS ≥ 0.1 G/l group: 7.0 months, and in stage IV, EOS < 0.1 G/l group: 5.0 months. EOS < 0.1 G/l (vs. ≥0.1 G/l) was an independent prognostic factor for OS in both the uni- and multivariate Cox regression, respectively (HR = 1.48, p = 0.035 and HR = 1.57, p = 0.021). (4) Conclusions: Peripheral eosinophilia seems to be a potential independent prognostic factor. Further studies are necessary to confirm this hypothesis, since our findings suggest that type 2 inflammation may be the factor directly or indirectly lengthening the survival of patients with PDAC.